2018
DOI: 10.1021/acs.langmuir.8b02711
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Physicochemical Changes of Carbonate Surfaces from SmartWater (Diluted Seawater) Flooding Processes for Improved Oil Recovery

Abstract: Over the past few decades, fieldand laboratory-scale studies have shown enhancements in oil recovery when reservoirs, which contain highsalinity formation water (FW), are waterflooded with modified-salinity salt water (widely referred to as the low-salinity, dilution, or SmartWater effect for improved oil recovery). In this study, we investigated the time dependence of the physicochemical processes that occur during diluted seawater (i.e., SmartWater) waterflooding processes of specific relevance to carbonate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…In general, calcite and other natural mineral surfaces display some degree of roughness at a molecular scale. Several studies have shown that surface roughness affects the water wettability of calcite [45,46] and oil desorption from calcite surfaces [47]. It, also, influences the interfacial forces between mineral surfaces in molecular scale.…”
Section: A) B)mentioning
confidence: 99%
“…In general, calcite and other natural mineral surfaces display some degree of roughness at a molecular scale. Several studies have shown that surface roughness affects the water wettability of calcite [45,46] and oil desorption from calcite surfaces [47]. It, also, influences the interfacial forces between mineral surfaces in molecular scale.…”
Section: A) B)mentioning
confidence: 99%
“…As a result, the additional volume of oil may be produced depending on the salinity level and ionic composition of intrinsic and injecting brine in the porous medium, , initial rock wetting preference, chemical activity of the rock surface, ,, thermodynamic conditions of the core flooding experiment, ,,, and physicochemical properties of the oil–rock–brine (ORB) system, among others. The effectiveness of MSW flooding in reducing the adhesion force between oil and rock surface and possible improvement of oil recovery depends on the alteration of physicochemical equilibrium at the subpore scale. ,,, Figure illustrates different scales relevant to MSW flooding. At the pore scale, a trapped oil droplet adhered to the rock through a thin formation water film can be mobilized by the alteration of the equilibrium condition at the rock–water–oil interface.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…A 25 times dilution of seawater did not show any impact on the wetting tendency of dolomite patches, while the contact angle for limestone changed in the order of 5°–17° over 100 h. In another study with a similar procedure, Mahani et al observed that kinetics of oil detachment from the fabricated clay patches during the exposure to low salinity brine was slower than the expected time for a process that is controlled by molecular diffusion. Chen et al monitored the dynamic and static contact angle of an oil droplet surrounded by MSW on a fully aged calcite surface. It was reported that in <15 min there was a rapid but slight increase in water wetness of the calcite surface that they attributed to the rapid increase in the electrostatic double-layer repulsion.…”
Section: Introductionmentioning
confidence: 99%
“…This is justified in that dolomite can be rendered oil-wet by carboxylates and that the oil-wetness can be reversed more effectively by cationic surfactants than anionic ones, similar to the other types of carbonate rocks. 11−16 However, compared to the extensive literature on the wettability alteration by potential determining ions (PDIs) and their application for EOR in calcite-based carbonate rocks (including those containing both calcite and dolomite minerals 17 ), very few systematic studies on the effect of PDIs on dolomite wettability have been reported. 18 A number of reports have identified that dolomite and calcite share the same PDIs, 19−23 namely, Ca 2+ , Mg 2+ , and SO 4 2− .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Most academic interest has been devoted to the precipitation and dissolution of the dolomite mineral, known as the “dolomite problem”. By contrast, in terms of EOR and, particularly, the mechanism of the wettability alteration, dolomite is often grouped together with calcite and aragonite into a collective concept of carbonate rocks and is believed to exhibit the same general wetting behavior as the other two calcium-rich mineral types. This is justified in that dolomite can be rendered oil-wet by carboxylates and that the oil-wetness can be reversed more effectively by cationic surfactants than anionic ones, similar to the other types of carbonate rocks. However, compared to the extensive literature on the wettability alteration by potential determining ions (PDIs) and their application for EOR in calcite-based carbonate rocks (including those containing both calcite and dolomite minerals), very few systematic studies on the effect of PDIs on dolomite wettability have been reported . A number of reports have identified that dolomite and calcite share the same PDIs, namely, Ca 2+ , Mg 2+ , and SO 4 2– .…”
Section: Introductionmentioning
confidence: 99%